Reciclando identidades laborais: um estudo com agricultores familiares pluriativos da Cooperativa de Recicladores de Materiais Orgânicos e Inorgânicos de Santa Cecília do Sul/RS - Virgolin, Isadora Wayhs Cadore (2016)
This study focuses on the themes of work identity and pluriactivity. The phenomenon of pluriactivity in rural areas is characterized by the combination of one or more economic activities, besides agriculture, carried out by one or more members of the same family. Within this context, the study was conducted with family farmers that combine their agricultural activity with their occupation as recyclers in a recycling cooperative, called Cooperativa dos Recicladores de Resíduos Orgânicos e Inorgânicos (Copercicla), located in the countryside of Santa Cecília do Sul, in the Northeast region of the State of Rio Grande do Sul. The general purpose of the study was to analyze the impact of the pluriactive work done by family farmers linked to Copercicla in their work identity. The research is characterized as a qualitative case study of descriptive and interpretative type. We conducted a literature review of the main authors that address the core issues of the study (Identity and Pluriactivity) and other topics related to the studied reality recycling in order to support the main categories of research analysis. Empirical data were collected by conducting observations, research in documentary sources, individual in-depth interviews, and group interviews. The data were organized and analyzed using content analysis. The survey results showed that the country has undergone significant changes, and that pluriactivity (and hence its effects) is a demonstration of such changes to which families resort specially to ensure their social reproduction. It was found that the condition of pluriactive workers that combine work activities in both agriculture and recycling brought changes in the identification process of the subjects and resized some aspects, starting with the provision of the family farmers in dealing with the implications of membership of the association work and the involvement with recycling activity impregnated with stigmas and prejudices that demanded and still demands of workers the deconstruction of such behavior in society. It is noted that the work activity on Copercicla has proven capable of promoting a different sociability that goes beyond the family environment that the farmers were used to. However, the resizing of the identity of these workers occurs without avoiding the identification with the rural activity, whose experience is seen as a relevant factor for the success of the Cooperative as well as the adaptation of workers in the recycling activity. Negative and positive aspects and characteristics of both occupations are linked, setting up a dynamic labor identification process that confirms the increasingly plural feature of the countryside areas nowadays.